The problems of work [soundrecording] : scientology applied to the workaday world - Hubbard, L. Ron [ (La Fayette Ron)] , 1911-1986 (Golden Era Productions, 2007)
From the publishers website: Containing the senior principles and laws which apply to every problem of work, here are the discoveries which lay bare the core of these problems and explain the very fabric of life itself. Learn the "secret" of efficiency. Find out the rock-bottom cause of exhaustion, how to eliminate it and return the energy of youth